Capital Structure and Firm Value Manufacturing at the Indonesian Stock Exchange - Murni, Sri (Archives of Business Research, 2022)
This study aims to determine and analyze the factors that influence the capital structure (asset structure, firm size, profitability) and its effect on firm value. The analysis was conducted on 51 manufacturing companies listed on the Indonesia Stock Exchange (IDX) using financial statement data from 2014 to 2019. The sample was taken by purposive sampling of 51 companies for 6 years of observation, using path analysis. The results show that the asset structure has a significant and positive effect on capital structure, firm size has a negative and significant effect on capital structure, and ROE has no significant effect on capital structure, also asset structure has an insignificant and negative effect on firm value, firm size and ROE have insignificant effect on firm value, and capital structure has no significant effect on firm value.